1997
DOI: 10.1002/(sici)1096-9861(19970915)386:1<119::aid-cne11>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Development of nicotinic receptor clusters and innervation accompanying the change in muscle phenotype in the mouse esophagus

Abstract: During development, the external muscle of the mouse esophagus undergoes a transdifferentiation from smooth to striated muscle (Patapoutian et al. [1995] Science 270:1818-1821). We now report on the development of the innervation accompanying the change in phenotype of the external muscle of the mouse esophagus. The phenotype of the muscle was monitored by using light and electron microscopy. Nicotinic acetylcholine receptors were localised by using a fluorescence conjugate of alpha-bungarotoxin, and neural el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
64
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 33 publications
6
64
1
Order By: Relevance
“…Previous results have shown that esophageal SM cells fail to transdifferentiate into striated muscle in Myf5 -/-:MyoD -/-embryos, even though this finding appears to occur in the wild-type esophagus (Patapoutian et al, 1995;Sang and Young, 1997;Kablar et al, 2000). Furthermore, SM cells in the esophagus have been shown to contain subtypes M1-M5 of mAChR (Wang et al, 2000), whereas subtype M2 has been identified on the esophageal enteric nerve terminals (Neuhuber et al, 2001).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Previous results have shown that esophageal SM cells fail to transdifferentiate into striated muscle in Myf5 -/-:MyoD -/-embryos, even though this finding appears to occur in the wild-type esophagus (Patapoutian et al, 1995;Sang and Young, 1997;Kablar et al, 2000). Furthermore, SM cells in the esophagus have been shown to contain subtypes M1-M5 of mAChR (Wang et al, 2000), whereas subtype M2 has been identified on the esophageal enteric nerve terminals (Neuhuber et al, 2001).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, SM cells in the esophagus have been shown to contain subtypes M1-M5 of mAChR (Wang et al, 2000), whereas subtype M2 has been identified on the esophageal enteric nerve terminals (Neuhuber et al, 2001). By contrast, the appearance of nAChR clusters coincides with the expression of a striated muscle phenotype (Sang and Young, 1997). To determine whether SM cells of the double-mutant esophagus nonetheless undergo a transition from mAChRs to nAChRs, FITC-␣-bungarotoxin staining and antinAChR immunohistochemistry was performed on relevant embryonic stages (i.e., E15.5-E18.5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations